1988
DOI: 10.1002/1097-0142(19881115)62:10<2191::aid-cncr2820621020>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer in a high-risk area in italy: Histopathologic patterns according to Lauren's classification

Abstract: Two thousand five hundred forty cases (1628 males and 912 females) of primary gastric cancer (GC) histologically diagnosed in gastroscopic biopsy or resected specimens, occurring from 1973 to 1982 in a high risk area in Italy (Florence), were reviewed. According to Lauren's criteria, 1587 (62.5%) were classified as intestinal type, 624 (24.6%) as diffuse type and 329 (12.9%) as mixed unclassified. The intestinal type is more frequent in males and increases in both sexes with advancing age; conversely for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Clear parallel declines of both histologic types among Connecticut women (Munoz and Connelly, 1971) correspond with a Swedish case series with no evidence of diverse secular trends for the two types over a 30-year period (1951-1981) (Lundegardh et al, 1991). Our results are, however, at odds with the decreasing ratios between the intestinal and diffuse types reported from the USA (Antonioli and Goldman, 1982), Norway (Munoz and Asvall, 1971), Germany (Mennicken et al, 1986), Italy (Amorosi et al, 1988), Finland (Lauren and Nevalainen, 1993), Iceland (Nikulasson et al, 1992), Japan (Hanai and Fujimoto, 1982) and Peru (Beteta et al, 1993). It is noteworthy that none of these studies were stratified for tumour site and most relied on hospital case series or registry data with a lower proportion of specimens classified histologically.…”
Section: Discussionsupporting
confidence: 54%
“…Clear parallel declines of both histologic types among Connecticut women (Munoz and Connelly, 1971) correspond with a Swedish case series with no evidence of diverse secular trends for the two types over a 30-year period (1951-1981) (Lundegardh et al, 1991). Our results are, however, at odds with the decreasing ratios between the intestinal and diffuse types reported from the USA (Antonioli and Goldman, 1982), Norway (Munoz and Asvall, 1971), Germany (Mennicken et al, 1986), Italy (Amorosi et al, 1988), Finland (Lauren and Nevalainen, 1993), Iceland (Nikulasson et al, 1992), Japan (Hanai and Fujimoto, 1982) and Peru (Beteta et al, 1993). It is noteworthy that none of these studies were stratified for tumour site and most relied on hospital case series or registry data with a lower proportion of specimens classified histologically.…”
Section: Discussionsupporting
confidence: 54%
“…No systematic differences between diagnoses based on surgery vs endoscopy were evident, however, so using diagnoses based on either procedure should not differentially bias results. A previous review of 297 GC patients in Florence reached a similar conclusion (Amorosi et al, 1988).…”
Section: Discussionmentioning
confidence: 52%
“…Several studies have suggested that the decline in the incidence of gastric cancer is due to a decrease of the Lauren intestinal-type (Munoz and Connelly, 1971;Amorosi et al, 1988;Nikulasson et al, 1992;Lauren and Nevalainen, 1993). However, these studies were mostly based on the proportional frequency ratio of the intestinal and diffuse types which does not itself indicate trends of incidence.…”
Section: Discussionmentioning
confidence: 99%